PENINGKATAN KUALITAS PELAYANAN KEPERAWATAN MELALUI RONDE DAN PENDOKUMENTASIAN - Rohita, Tita; Yetti, Krisna (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
Ronde nursing and completeness of documentation of nursing care is part of the quality ofnursing care in the hospital. Interest-round optimization of the implementation of nursing andnursing care documentation that is refreshing and prepare the necessary tools. So that theknowledge and commitment to change for the better. The method to do that is by using a casestudy approach of PDC). Result the program , the nurse's knowledge increases with pre-testresults of 68% to 85% shows good improvement that could indicate that the implementation iscarried out is considered effective to increase the knowledge of nurses.. Increased training,increased technology strategy nursing human resources management, periodic evaluationworkload, create an enabling environment conducive work culture is also very important role inoptimizing the program.